1982
DOI: 10.1111/j.1365-2265.1982.tb02638.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal LHRH Agonist Treatment for Inhibition of Ovulation in Women: Clinical Aspects

Abstract: Daily intranasal administration of the potent stimulatory LHRH analogue D-Ser(TBU)6-EA10-LHRH was given to fifty healthy women for 3 months. Twenty-six women received 400 micrograms LHRH agonist/day and twenty-four women received 600 microgram/day. Inhibition of ovulation occurred during 147 of the 150 treatment months. The three presumptively ovulatory cycles were probably the result of initial technical problems with the nasal spray. No pregnancies occurred. Reactivation of corpus luteum with slightly raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nevertheless, ovulation did not occur in these patients, as indicated by the absence of progesterone secretion. The recurrence of estradiol secretion was also found in about 75-85% of the women in studies where the efficacy of lower doses of LHRH analogues was investigated with respect to contraception (35)(36)(37). In those studies progesterone secretion appeared not completely suppressed in all women (10-15% of treatment cycles) during chronic treatment with lower intranasal doses of 400-600/xg per day.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, ovulation did not occur in these patients, as indicated by the absence of progesterone secretion. The recurrence of estradiol secretion was also found in about 75-85% of the women in studies where the efficacy of lower doses of LHRH analogues was investigated with respect to contraception (35)(36)(37). In those studies progesterone secretion appeared not completely suppressed in all women (10-15% of treatment cycles) during chronic treatment with lower intranasal doses of 400-600/xg per day.…”
Section: Discussionmentioning
confidence: 85%
“…However, during the combination therapy we sometimes observed peaks of LH and FSH, followed in some patients by ovarian progesterone secretion, so that the stimulatory effect of tamoxifen on the pituitary gonadal axis (32) may overcome the suppressive effect of the doses of LHRH agonist used. A point of concern is the potential fertility of patients on this combined endocrine treatment; addition of tamoxifen may annihilate the advantage of contraception caused by single treatment with Buserelin (35)(36)(37), unless the endometrial changes caused by long-term tamoxifen treatment (34) prevent gravidity.…”
Section: Discussionmentioning
confidence: 99%
“…Low agonist doses do not block FSH secretion and ensure adequate follicular maturation with oestradiol rises. In clinical studies with buserelin administered by nasal spray, treatment was well accepted and consistent inhibition of ovulation was reported (Bergquist et al, 1979b(Bergquist et al, ,c, 1982Schmidt-Gollwitzer et a/., 1981b. There was a wide range of bleeding patterns but absence of dysfunctional bleeding.…”
Section: Inhibition O F Ovulationmentioning
confidence: 78%
“…Thus, for instance, the dose of 1200 /ig given intranasally by Klijn and co-workers corresponds to only approximately 25 Mg given parentally. Studies in which GnRH analogs were investigated with respect to contraception have also indicated that intranasal administration (400-600 ng/ day) is unable to totally suppress ovarian hormone production in the majority of women (13)(14)(15). Thus, at present, it appears that complete castration can only be achieved with chronic administration of large doses of GnRH analogs parenterally.…”
Section: February 1986mentioning
confidence: 91%